Settling of copper-rich suspended particles from acid drainage neutralization as a function of chemical composition and particle size distribution. (April 2022) - Montecinos, Mauricio; Briso, Alejandro; Vega, Alejandra; Pastén, Pablo
Abstract: The attenuation of total and dissolved metals from acid drainage (AD) results from the interaction of physical and chemical processes occurring during and after AD neutralization in impacted rivers. Chemical removal occurs when dissolved metals are transferred into fine particles or flocs, while physical removal occurs when metal-rich suspended particles are deposited from the water column onto the riverbed. Most works studying metal attenuation in rivers focus on characterizing chemical and physical removal processes separately, yet these processes often interact and take place concurrently. The fate of copper (Cu) in particle suspensions formed from partial neutralization of AD was studied using a settling column coupled to a device that measured particles size distribution in situ, with minimal floc disruption. Chemical composition, particles size distribution, and total suspended solids (TSS) were measured as particles settled. The physical removal of freshly formed particles was enhanced by aluminum (Al), promoting the formation of larger particles and higher rates of TSS removal. However, Fe promoted higher partition of Cu onto particles, controlling its chemical removal. While the rate of Cu association to particles increased over time, TSS settled out from solution within the initial hour, regardless of the chemical composition within the range of tested conditions. Therefore, different remediation strategies may be applied depending on the goal for removal (e.g., removal of TSS, removal of Cu) and water composition. These strategies must consider chemical conditions (i.e., pH and concentrations of Al and Fe), settling times, and mixing conditions during particles formation for an optimal removal. Graphical abstract: Image 1 Highlights: Fe and Al impact differently on the physical and chemical removal of Cu at pH 5.5 Al forms suspensions with higher TSS concentration and larger d50 . Fe controls chemical removal by increasing the sorption of Cu. Systems with a settling stage of more than 80 min favor particle removal. Systems with flocculation stage of less than 20 min constrain Cu sorption.